Thomas Aquinas's Summa Contra Gentiles : a guide and commentary - Davies, Brian, 1951- (Oxford University Press, 2016)
Presupposing no previous knowledge of Aquinas or of his works, the author offers an account and discussion of the Summa Contra Gentiles.